Improving Reading Comprehension of the Grade Viii Students of SMPN 14 Palu Through Scanning Technique: Meningkatkan Pemahaman Membaca Siswa Kelas VIII SMPN 14 Palu Melalui Tekhnik Memindai - Indah Permatasari; Nur Sehang Thmarin; Fikriani A. Omolu (Universitas Muhammadiyah Palu, 2021)
This research aims at improving students’ reading comprehension in English lesson by using scanning technique. This research is design as a quasi-experimental research. Population of this research was grade VIII students of SMPN 14 Palu and sample was 56 students that consist of 28 students from Cut Nyak Dien class and 28 students from Hasanudin class. The sample was taken by applying purposive sampling technique. Students from Cut Nyak Dien class are classified into experimental group, while Hasanudin class’ students are into control group. Research findings show that the t-counted was 3.268. By using level of significance 0.05 and the degree of freedom was 54, the t-table found is 2.015. This result indicates the t-counted value was higher than the t-table value. It means that the research hypothesis is accepted. In other words, the application of the scanning technique can effectively improve students’ reading comprehension.